Nurses' viewpoints on incivility in nursing in Iran - Leila Malekyan; Hadi Khoshab; Mohammad Ghazanfarabadi; Mohammad Javad Rahimzadeh (Elsevier, 2022)
Background: Incivility behaviors in work environments are a serious threat and lead to shame and endanger the health of nurses and patients. Aim: The purpose of this study was to evaluate nurses' viewpoints on Incivility behaviors in clinical setting in Bam University of Medical Sciences. Method: This descriptive cross-sectional study was done on 221 nurses working in Pasteur Hospital in Bam. Data were collected through a demographic questionnaire and Nursing Incivility Scale by census sampling after obtaining the consent of the participants. Data were analyzed by SPSS 19 software using descriptive statistics, independent t-test, one-way ANOVA, Bonferroni post hoc and Spearman correlation tests with 95% confidence interval. Result: The results of this study showed that the mean score of uncivil behavior among nurses was 85.99 ± 27.26. The most uncivil behaviors in nurses were related to interaction with patients and visitors (20.79 ± 8.01), and the lowest uncivil behavior was related to interaction with supervisors (13.46 ± 6.29). Results indicated that nurses experience moderate levels of Incivility. Conclusion: Religious differences as one of the determinants of the occurrence of Incivility can lead to job pressures and job dissatisfaction. Therefore, specific attention should be paid to the factors that lead to the emergence of uncivil behavior in nurses' work environment. With training of religiosity, the strengthening of religious beliefs and religious conciliatory, it is possible to reduce the incidence of uncivil behaviors.